Aplikasi Belajar Mengenal Rumah Adat Di Indonesia Menggunakan Teknologi Augmented Reality Berbasis Android - Helmi Fikry Haikal; Joko Aryanto (STMIK Budi Darma, 2023)
A traditional house is a cultural heritage in Indonesia that we can get to know and learn about the meaning and function of a traditional house. Knowing or studying a traditional house is the same as studying the cultural heritage of a country, of course Indonesia. This research aims to help learning or introduction to culture or traditional houses in Indonesia by using Augmented Reality Technology and using the markerless method and using the markerbased method which can be used without certain media or objects for markerless, while the markerbased method can use media or image to show a three-dimensional image or plane. With this application, it is hoped that users will be able and easier to learn what is called a traditional house, where the traditional house comes from and the structure of the building and see it in 3 dimensions